2010
DOI: 10.1021/es103026a
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Riverine Material Loads and Environmental Consequences on the Changjiang (Yangtze) Estuary in Recent Decades (1955−2008)

Abstract: With intense anthropogenic perturbations in the Changjiang (Yangtze) River basin, the riverine loads and compositions of materials into the Changjiang Estuary have greatly changed, resulting in dramatic deterioration in the Changjiang Estuary and adjacent sea environments. Based on a long-term data set of the material loads into the Changjiang Estuary, changing trends and associated impacted factors were presented. The results showed downward trends concentrations and loads of dissolved silicate (DSi) over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
174
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(182 citation statements)
references
References 24 publications
7
174
1
Order By: Relevance
“…It is not possible to re-do the flux calculations, say, based on the same gas exchange coefficient, as the original data were not provided in the papers cited. Further, there is a lack of temporal coverage as previous studies (Bozec et al, 2011;Dai et al, 2009;Kitidis et al, 2012) have demonstrated short-term changes in pCO 2 at scales of days or less. Yet, typically data on such a scale are limited to only a few cruises.…”
Section: Sea-to-air Co Fluxes In Estuariesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not possible to re-do the flux calculations, say, based on the same gas exchange coefficient, as the original data were not provided in the papers cited. Further, there is a lack of temporal coverage as previous studies (Bozec et al, 2011;Dai et al, 2009;Kitidis et al, 2012) have demonstrated short-term changes in pCO 2 at scales of days or less. Yet, typically data on such a scale are limited to only a few cruises.…”
Section: Sea-to-air Co Fluxes In Estuariesmentioning
confidence: 99%
“…The numerical average an- nual flux per unit area, however, is not used to calculate the global release of CO 2 because small estuaries dominate the numerical average, but they contribute relatively little to the total flux. Important to note is that there is a lack of temporal coverage in most of the data sets although previous studies (Bozec et al, 2011;Dai et al, 2009;Kitidis et al, 2012) have demonstrated short-term changes in pCO 2 at scales of days or less. Yet, typically data on such a scale are limited to only a few cruises.…”
Section: Sea-to-air Co Fluxes In Estuariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The precipitation measured in 2006 at some stations (e.g. Cuntan, Beibei) was as much as 30% lower than that in normal years (CRWRC, 2007, Dai et al 2010b. The flood season in the Yangtze River lasts from May to October and the dry season from November to April (Liu et al 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Most studies indicate that dam constructions have led to a significant impact on the decrease of SSD in rivers (Vörösmarty et al 2003, Walling and Fang 2003, Dai et al 2010b, Yang et al 2010. As a consequence of the upstream obstruction due to dams, notable reductions of SSD into the estuaries of large rivers, such as the Nile, Mississippi, Colorado, Ebro and Yellow rivers have been reported (Sánchez et al 1998, Carriquiry et al 2001, Frihy et al 2003, Yang et al 2004, Syvitski et al 2005.…”
Section: Introductionmentioning
confidence: 99%